Contribution of intellectual capital strategic readiness and government innovation - Ali, Hasrati; Sofyan Idris, Abdul Rahman Lubis, Nurdasila Darsono, (Opción, 2019)
The purpose of this study was to determine the effect of highperformance work systems on the performance of government administration, which is mediated by the strategic readiness of human capital and government innovation capabilities. The data obtained were analyzed qualitatively by quantitative grooming with Structural Equation Modeling and Confirmatory Factor Analysis methods. The results showed that there was a significant effect between the highperformance work system on the performance of governance and the strategic readiness of human capital. In conclusion, Intellectual Capital Strategic Readiness is not strong enough to mediate the relationship between High-Performance Work Systems and Government Management Performance.